Concurrence of Inappropriate Antidiuretic Hormone Secretion and Cerebral Salt Wasting Syndromes after Traumatic Brain Injury - Shen, Bo; Li, Lin; Li, Ting (Frontiers in Neuroscience, 2017)
Syndrome of inappropriate antidiuretic hormone (SIADH) and cerebral salt wasting syndrome (CSWS) as the two most common neuroendocrine diseases, have been recognized and understood by many neurologists.Although SIADH and CSWS are the common causes of central hyponatremia after traumatic brain injury (TBI), a few cases are mixed, with the coexistence of the two pathological pathomechanism. However, the mixed type of both SIADH and CSWS has not been clearly reported in any literature. Here,we present the first description of the concurrent syndrome of SIADH and CSWS after TBI in four patients who underwent standard diagnostic procedures, treatment and follow up. Our findings further support that this rare neuroendocrine disease may exist in clinical practice, in which the traditional-conventional treatment shows poor efficacy.